Entre escolas : a trajetória escolar de estudantes com deficiência intelectual a partir da percepção das mães - Oliveira, Claudia Medeiros de (My University, 2016)
The schooling of the intellectual disabled is a recurring theme in the educational context and it has raised numerous concerns and considerations on its regard. Studies on the subject, commonly address the issue from teachers and legislation's perspective that aims to ensure the education of the disabled. In order to contribute with the reflections from another perspective, this dissertation, part of the field of Education studies, aims to analyze how mothers perceive the schooling process of their intellectually disabled child. The study also tries to trace the school history of the student between regular school and special school, to identify aspects that sustain the family's choices regarding this path. The objective was also to identify principles that contribute to the student with intellectual disabilities' educational process. The research consists of a qualitative study of exploratory nature, based on the premises of Vigotski's Historical-Cultural Psychology, particularly his studies on Defectology and counted with interviews as a data construction tool. Interviews were conducted with six mothers of students with intellectual disabilities, aged between 10 and 17 years old, residing in the city of Caxias do Sul. For carrying out the analysis of the collected data, Bardin's content analysis was used, in which four categories were identified: a) Trajectory School, b) Perceptions of mothers towards the child, c) Perceptions of mothers regarding the teachers and d) Perception of mothers regarding Inclusion. The results indicate that the schooling of intellectual disabled people constitutes a path permeated by difficulties and achievements from both the student and the family and school. The speeches of mothers reveal an educational panorama still ruled by the traditional model, in which stands the pursuit for a standardization of the student, but also, in an incipient way, there is movement on the part of some parents and teachers that look for a reformulation of this scene by constructing different possibilities for schooling ID people.
A trajetória escolar do estudante com deficiência intelectual é tema recorrente no contexto educacional e tem gerado inúmeras inquietações e ponderações a seu respeito. Os estudos realizados na área comumente abordam o tema a partir da perspectiva do docente e da legislação que busca garantir a escolarização do deficiente. Visando contribuir com as reflexões a partir de outra ótica, esta dissertação, inserida no campo dos estudos da Educação, tem como objetivo analisar como as mães percebem a trajetória escolar de seu filho com deficiência intelectual. O estudo também busca traçar a trajetória escolar do estudante entre a escola comum e a escola especial, visando identificar os aspectos que sustentam as escolhas da família com relação a essa trajetória. Objetivou-se, ainda, traçar princípios que contribuam no processo de escolarização do estudante com deficiência intelectual. A pesquisa consiste em um estudo qualitativo de natureza exploratória, embasada nos preceitos da Psicologia Histórico-Cultural de Vigotski, em especial, seus estudos sobre a Defectologia e contou com entrevistas como instrumento de construção de dados. As entrevistas foram realizadas com seis mães de estudantes com deficiência intelectual, com idade entre 10 e 17 anos, residentes no município de Caxias do Sul. Para a realização da análise dos dados coletados, utilizou-se a análise de conteúdo de --5Bardin, em que foram identificadas quatro categorias: a) Trajetória Escolar, b) Percepções das mães em relação ao filho, c) Percepções das mães em relação aos docentes e d) Percepções das mães em relação à Inclusão. Os resultados apontam que a trajetória escolar do estudante com deficiência intelectual ainda é permeada por preconceitos e pela busca da normalização deste sujeito. O discurso das mães evidencia a vigência do modelo tradicional de ensino-aprendizagem, prevalecendo um olhar sustentado pelos modelos caritativo e médico da deficiência nas orientações quanto ao processo de escolarização deste estudante. Mas, também se observa movimentos incipientes que visam a reestruturação do cenário como a aceitação das diferenças por parte dos docentes estabelecendo um novo olhar sobre a inclusão e a ressignificação das mães sobre o processo de aprendizagem, construindo possibilidades diferenciadas na trajetória escolar deste estudante.
Keywords: Mainstreaming in education; Inclusive education; Special education; Stupidity; Learning; Early childhood education - Parent participation; Mothers - Case studies; Inclusão escolar; Educação inclusiva; Educação especial; Incapacidade intelectual; Aprendizagem; Educação de crianças - Participação dos pais; Mães - Estudo de casos